MEMBANGUN KODE GOLAY (24, 12, 8) DENGAN MATRIKS GENERATOR DAN MENGGUNAKAN ATURAN KONTRUKSI - rizki, ikhsan; Irawanto, Bambang (MATEMATIKA, 2010)
The binary (24, 12, 8) extended Golay code can be constructed through the direct sum operation with involve two product codes. This method form the generator matrix framework of the (24, 12, 8) Golay code that is based on the so-called Turyn or |a + x|b + x|a + b + x| construction, where a,b C1 and x C. C1 and C is the (8, 4, 4) linear block codes. C can be gotten by applying construction rules to get the generator matrix of C. With C1 and C and by applying the generator matrix framework of the (24. 12, 8) Golay code get the binary (24, 12, 8) extended Golay code.